2009
DOI: 10.1002/jts.20447
|View full text |Cite
|
Sign up to set email alerts
|

Social relations and PTSD symptoms: A prospective study on earthquake‐impacted adolescents in Taiwan

Abstract: This prospective longitudinal study examined two competing models, a traditional social support model and a supportive and detrimental social relations model, to clarify the association of PTSD symptoms with supportive and detrimental social relations. Seven-hundred five adolescents living near the epicenter of the Taiwan Chi-Chi Earthquake participated in the study. The models were evaluated and cross-validated using structural equation modeling. The supportive and detrimental social relations model appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…This is in agreement with previous researchers' findings which show that social support was negatively related to posttraumatic stress disorder (PTSD) (Bradley, Schwartz & Kaslow, 2005;Brewin, Andrews & Valentine, 2000;Hersberger & D'Augelli, 1995;Ozbay, et al, 2007;Ozer et al 2003;Pine & Cohen, 2002;Wu et al, 2009). In this study, social support was found to moderate the relationship between exposure to violence and PTSD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with previous researchers' findings which show that social support was negatively related to posttraumatic stress disorder (PTSD) (Bradley, Schwartz & Kaslow, 2005;Brewin, Andrews & Valentine, 2000;Hersberger & D'Augelli, 1995;Ozbay, et al, 2007;Ozer et al 2003;Pine & Cohen, 2002;Wu et al, 2009). In this study, social support was found to moderate the relationship between exposure to violence and PTSD.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have shown that social support was negatively related to posttraumatic stress disorder symptoms among victimized or maltreated youths (Bradley, Schwartz & Kaslow, 2005;Brewin, Andrews & Valentine, 2000;Hershberger & D'Augelli, 1995;Ozer, Best, Lipsey & Weiss, 2003;Pine & Cohen, 2002;Wu, Chen, Weng & Wu, 2009). A number of studies have shown that social support mediates or moderates the relation between children and adolescents' exposure to violence, victimization or maltreatment and PTSD symptoms (Bradley, Schwartz & Kaslow,2005;Ozbay, Johnson, Dimoulas, Morgan, Charney & Southwick, 2007;Wu, Chen, Weng & Wu, 2009). For instance, Ozbay et al, (2007) found that rich social networks may reduce the rate at which individuals engage in risky behaviours, prevent negative appraisals and increase treatment adherence and likelihood of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Each item is rated on a 5-point Likert scale ranging from 0 (none of the time) to 4 (most of the time), reflecting the frequency of occurrence of a particular symptom during the past month. The Chinese version of the UCLA PTSD Reaction Index was adapted using a back-translation procedure that has been validated and widely used in Chinese populations (e.g., Chen & Wu, 2006;Jia et al, 2010;Wu, Chen, Weng, & Wu, 2009). In the present study, participants were instructed to complete the index in relation to their experiences of the earthquake, and Cronbach's  was 0.88 for the PTSD symptom scale in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, youth in Chinese societies are expected to have both enhanced needs for social support and increased risks for developing low self-esteem and a sense that others value them less when experiencing traumas that threatens social connection. Current research evidence has provided preliminary support that self-blaming was one main coping style used by Chinese adolescent survivors with an increased risk for PTSD (Zhang et al 2010) and has also shown that Taiwanese youth perceived great distress from negative appraisals of detrimental soci al relationships (Wu et al 2009). Development of a culturally sensitive measure is a prerequisite to understanding youth' trauma-related cognitions in Chinese cultural contexts.…”
Section: Chinese Cultural Effects On Youth' Response To and Evaluatiomentioning
confidence: 97%